2007
DOI: 10.1103/physrevc.75.054612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preequilibrium spin distribution onTi48+ncross sections

Abstract: Nuclear model calculations of discrete γ -ray production cross sections produced in 48 Ti(n, n γ i ) 48 Ti and 48 Ti(n, 2nγ i ) 47 Ti reactions were made as a function of incident neutron energy from E n = 1 MeV to 35 MeV and compared with new experimental results using the large-scale Compton-suppressed germanium array for neutron induced excitations (GEANIE) at LANSCE. The Hauser-Feshbach reaction code GNASH, incorporating the spin distribution for the preequilibrium process calculated with the FeshbachKerm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…The same contribution can be also observed in panel d) where we can see an increase in the value of the cross section around 9 MeV. This is also the main difference between our experimental results and the results of Dashdorj et al [8] and it comes from the fact that they used an enriched 48 Ti sample. All the cross sections reported here have maximum values above 1.2 b and total relative uncertainties around 5% except the one for 49 Ti where the cross section is around 0.2 b.…”
Section: Theoretical Considerationssupporting
confidence: 79%
See 1 more Smart Citation
“…The same contribution can be also observed in panel d) where we can see an increase in the value of the cross section around 9 MeV. This is also the main difference between our experimental results and the results of Dashdorj et al [8] and it comes from the fact that they used an enriched 48 Ti sample. All the cross sections reported here have maximum values above 1.2 b and total relative uncertainties around 5% except the one for 49 Ti where the cross section is around 0.2 b.…”
Section: Theoretical Considerationssupporting
confidence: 79%
“…Looking in the experimental nuclear reaction database EXFOR [7] we observe that most of the neutron inelastic scattering experiments on the titanium isotopes were performed between 1960 and 1980 in a limited energy range. The energy range was extended by Dashdorj et al [8] in 2007 when they determined the γ -production cross sections of the transitions observed from the inelastic scattering of the neutrons on 48 Ti up to E n = 200 MeV. Our goal was to measure the γ -production cross sections for the most important transitions in all of the stable Ti isotopes.…”
Section: Introductionmentioning
confidence: 99%
“…The Monte Carlo technique also facilitates new insights into the nuclear reaction, as correlations between different processes can be studied by gating on a particular γ-ray so as to provide useful information on spin and parity distributions in the continuum state [3]. Coincidence experiments, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recent results of γ-ray production cross section measurements at LANSCE performed with the GEANIE detector array [1] demonstrated that the spin distribution of the pre-equilibrium reaction has a large impact on the γ-ray transition probability when incident energies are above E n = 10 MeV [2,3]. Since it was previously assumed that the spin distribution in the preequilibrium process had a limited impact on nuclear reaction cross sections, classical theories such as the exciton model [4,5] are still widely used to analyze particle emission data at high incident energies.…”
Section: Introductionmentioning
confidence: 99%